2013
DOI: 10.1093/ndt/gft220
|View full text |Cite
|
Sign up to set email alerts
|

Atypical haemolytic uraemic syndrome with underlying glomerulopathies. A case series and a review of the literature

Abstract: Different types of glomerulopathies can be complicated by aHUS. Several mechanisms can contribute to this association, such as nephrotic-range proteinuria, mutations or aHUS-risk haplotypes involving genes encoding alternative complement regulatory proteins in some patients and inflammatory triggers associated with systemic immune-mediated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 77 publications
1
60
0
Order By: Relevance
“…Abnormalities in the regulation of the complement system, and particularly defects in the proteins that physiologically control the activity of the cAP, are responsible for most cases of aHUS, a form of TMA that can be associated with autoimmune diseases, such as lupus nephritis or other GN (10). Moreover, a correlation between C4d staining and TMA in lupus nephritis was previously described (17).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Abnormalities in the regulation of the complement system, and particularly defects in the proteins that physiologically control the activity of the cAP, are responsible for most cases of aHUS, a form of TMA that can be associated with autoimmune diseases, such as lupus nephritis or other GN (10). Moreover, a correlation between C4d staining and TMA in lupus nephritis was previously described (17).…”
Section: Discussionmentioning
confidence: 94%
“…Genetically determined defects of cAP regulatory proteins (e.g., complement factor H, membrane cofactor protein) are responsible for most cases of primary aHUS in adults, but aHUS can also be associated with systemic immunemediated disorders. In a recent literature review that also included original cases, we showed that aHUS can be associated with several types of vasculitis, particularly AAV, and that patients with aHUS overlapping with AAV usually have a poor outcome (10). Histologic signs of TMA have been encountered in AAV, but there are no systematic studies, and the prognostic importance of these abnormalities is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Patient reports of C3G as the presenting feature with aHUS occurring later in the clinical course include an adult man with complete FH deficiency who presented with biopsyproven C3G (MPGN) but approximately 1 year later, developed aHUS 23 ; an individual with anti-FH autoantibodies who presented with C3G (MPGN) and developed recurrent C3G in the first renal transplant and TMA in the second transplant 24 ; a young man with mutations in both C3 and CD46 and a family history of aHUS who presented initially with C3G (MPGN) before developing clinical features of aHUS 25 ; a young man with a heterozygous FH mutation who presented with C3G (MPGN) and later developed aHUS 26,27 ; an adult woman with C3G (MPGN) with no complement mutations who later developed aHUS 27 ; and an adult man with C3G (mesangial C3 deposits) with no complement mutations who later developed concurrent aHUS. 27 Patient reports of aHUS as the presenting feature with C3G occurring later in the clinical course are less numerous but include a young man with combined heterozygous FH and FI mutations who presented with aHUS and subsequently developed glomerular C3 deposits in the transplant kidney 28 and a young man with homozygous FH deficiency who presented with aHUS and then developed isolated glomerular C3 deposits in the absence of TMA within the transplant kidney. 28 In this context, the hepatocyte-Cfh 2/2 mice recapitulate the clinical observations and provide definitive experimental evidence that the same genetic defect can predispose to C3G and aHUS.…”
Section: Discussionmentioning
confidence: 99%
“…Overt fibrin platelet thrombosis may be absent from renal biopsies of TMA, which has recently led to a suggested reclassification to microangiopathy with or without thrombosis (6). Evidence of TMA has also been reported in a number of glomerular diseases (7) and autoimmune diseases; however, in published clinicopathologic studies, only a small Figure 1. | Thrombotic microangiopathies are classified into: Inherited or acquired primary; secondary; or infection associated TMAs.…”
Section: Pathologymentioning
confidence: 99%